Liver X receptor regulates Th17 and RORγt+ Treg cells by distinct mechanisms - Parigi, Sara M.; Das, Srustidhar; Frede, Annika; Cardoso, Rebeca F.; Tripathi, Kumar Parijat; Doñas, Cristian; Hu, Yue O.O.; Antonson, Per; Engstrand, Lars; Gustafsson, Jan-Åke; Villablanca, Eduardo J. (Mucosal immunology, 2021)
The gastrointestinal microenvironment, dominated by dietary compounds and the commensal bacteria, is a major driver of intestinal CD4+ T helper (Th) cell differentiation. Dietary compounds can be sensed by nuclear receptors (NRs) that consequently exert pleiotropic effects including immune modulation. Here, we found that under homeostatic conditions the NR Liver X receptor (LXR), a sensor of cholesterol metabolites, regulates RORγt+ CD4 T cells in the intestine draining mesenteric lymph node (MLN). While LXR activation led to a decrease, LXR-deficiency resulted in an increase in MLN Th17 and RORγt+ Tregs. Mechanistically, LXR signaling in CD11c+ myeloid cells was required to control RORγt+ Treg. By contrast, modulation of MLN Th17 was independent of LXR signaling in either immune or epithelial cells. Of note, horizontal transfer of microbiota between LXRα−/− and WT mice was sufficient to only partially increase MLN Th17 in WT mice. Despite LXRα deficiency resulted in an increased abundance of Ruminococcaceae and Lachnospiraceae bacterial families compared to littermate controls, microbiota ablation (including SFB) was not sufficient to dampen LXRα-mediated expansion of MLN Th17. Altogether, our results suggest that LXR modulates RORγt+ Treg and Th17 cells in the MLN through distinct mechanisms.